STRATEGI OPTIMALISASI PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN BURU SELATAN - Djufri Rays Pattilouw (Jurnal Cita Ekonomika, 2018)
The purpose of this study was to evaluate the performance of Regional Original Revenue (PAD) and formulate a strategy in order to optimize PAD revenues in South Buru Regency. Related to PAD evaluation, the method of effectiveness ratio analysis, elasticity, and fiscal independence ratio were used. Meanwhile, to formulate PAD optimization strategy, a number of stages are taken in the SWOT analysis method. The results are: 1) The achievement of PAD in South Buru Regency is not good yet, as seen from the fiscal independency ratio, effectiveness ratio, and relatively low and uncertain PAD elasticity; 2) Strategic environmental maps show that management of PAD in South Buru is in quadrant III which is weak internally but has many opportunities that can be developed; 3) SWOT matrix conclude that the alternative strategy that must be a top priority for efforts to optimize the management of PAD in South Buru Regency is the W-O Strategy, namely: "Fixing weaknesses to optimize opportunities"